2015
DOI: 10.4236/psych.2015.614179
|View full text |Cite
|
Sign up to set email alerts
|

Study on Influence of Internal Working Models and Gender Differences on Addiction of Social Network Sites in Japanese University Students

Abstract: In recent decades, social network sites (SNSs) have become more popular and SNSs addiction has become a serious social problem. However, few studies have examined the effect of a person's internal working model (IWM) on addiction, which determine how attachment processes operate throughout the life course. This study aims at investigating the influence of IWMs and the psychological state, particularly loneliness and interpersonal trust, and of gender differences on addiction of SNSs in Japanese university stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…More specifically, secure individuals accept their own emotional needs (Estévez et al 2017), while insecure individuals do not (e.g., anxious-avoidant). The more they think they cannot rely on others' support (Estévez et al 2017), the more it leads to the avoidance of interpersonal relationships and they search for compensation via online engagement (Eichenberg et al 2017;Estévez et al 2017;Fujimori et al 2015;Lei and Wu 2007;Savcı and Aysan 2016;Yang et al 2016). This finding is in line with research suggesting that childhood trauma (e.g., physical and sexual abuse) can be a risk factor for internet addiction (Odacı and Çıkrıkçı 2014;Schimmenti et al 2014).…”
Section: The Influence Of Internet Addictionsupporting
confidence: 72%
“…More specifically, secure individuals accept their own emotional needs (Estévez et al 2017), while insecure individuals do not (e.g., anxious-avoidant). The more they think they cannot rely on others' support (Estévez et al 2017), the more it leads to the avoidance of interpersonal relationships and they search for compensation via online engagement (Eichenberg et al 2017;Estévez et al 2017;Fujimori et al 2015;Lei and Wu 2007;Savcı and Aysan 2016;Yang et al 2016). This finding is in line with research suggesting that childhood trauma (e.g., physical and sexual abuse) can be a risk factor for internet addiction (Odacı and Çıkrıkçı 2014;Schimmenti et al 2014).…”
Section: The Influence Of Internet Addictionsupporting
confidence: 72%
“…The following was referred to in Fujimori et al (2015) about attachment theory. Bowlby (1969) In general, there might be family functions issue or an attachment problem in addiction, substance abuse or conduct disorder conditions.…”
Section: Loneliness Attachment and Family Functionsmentioning
confidence: 99%
“…To prevent any leaking of personal information via survey assistants, participants responded anonymously to survey materials. The Ethical Review Committee of Kawasaki University of Medical Welfare approved this study .Over and above, this study was conducted at the same time with Fujimori et al (2015) and investigated SNSs addiction. Thus, measurements of loneliness and attachment as well as sample were duplicates.…”
Section: Samplementioning
confidence: 99%
“…One meta-analysis found that females were more likely to exhibit social media addiction and less likely to display Internet gaming disorder than males [ 35 ]. Since female adolescents often value relationships more than males, they tend to use the Internet for social networking in response to feelings of emptiness when their social needs are not otherwise fully met [ 36 ]. Once the threshold of Internet use increases, individuals require more time to reach the degrees of satisfaction previously achieved [ 37 ].…”
Section: Discussionmentioning
confidence: 99%